Raiul de sub glaja - Morar, Manuela (Romania, 2010)
In Gherla village, Cluj county, it turns out that as a consequence of the actions taken by the center of conservation and promotion of traditional culture, the inhabitants of the village in 2008 started painting. Through the eyes of Nicula, people who showed their interest in painting were given brushes, drawing pens, tempera color cases and the children were encouraged to attend courses in the local school and to participate at the annual painting camp of the county.
Verzio Film Festival Submission
Keywords: Documentary films